Disaster, displacement and resilient livelihoods : perspectives from South Asia - Islam, M. Rezaul (Diverse Perspectives on Creating a Fairer Society Series., 2023)
Covering disaster scenarios, and the causes and consequences of disaster displacement, Disaster, Displacement and Resilient Livelihoods: Perspectives from South Asiafocuses on the South Asian context, generating new insights and considering the policy implications of strategies for building resilient livelihoods.